Government Policies In Islamic Microeconomics - Laila, Ahrina; Misbahussururi, Adila; Panorama, Maya (Jurnal Fokus Manajemen, 2025)
Islamic Microeconomics prioritizes sharia principles that regulate economic activities in a fair and transparent manner. The method used in this study is descriptive analytical with a qualitative approach. Data was collected through literature reviews that included classical literature such as Ibn Khaldun's works, to modern documents from government and academic institutions. The results of research on government policies in Islamic microeconomics show that subsidies in the agrarian sector have a significant positive impact on the welfare of farmers in South Sumatra such as reducing production costs, increasing productivity, access to quality agricultural inputs such as superior seeds that encourage increased crop yields, increasing food security and reducing social inequality. Therefore, the role of the state is very important where government policies must support the achievement of the welfare of a just and prosperous society without contradicting the teachings of Islam